Radiative heat attenuation mechanisms for nanoporous thermal insulating composites. (25th July 2016) - Feng, Jinpeng; Wang, Youlan; Feng, Xia; Huang, Qiang; Ma, Shaojian; Mo, Wei; Yang, Jinlin; Su, Xiujuan; Lin, Meiqun
Highlights: Nanoporous thermal insulating composites are prepared by a dry molding method. SiC as an opacifier can reduce radiation heat transfer at higher temperatures. Radiation attenuation mechanisms are explained by calculating optical parameters. The calculation results are verified by thermal conductivity measurement. Abstract: Nanoporous thermal insulating composites of fumed silica, opacifier, and fiber have been prepared by a dry molding method. SiC is adopted as an opacifier to improve thermal insulating performance at higher temperatures where radiation heat transfer plays an important role in entire heat transfer system. Radiative heat attenuation mechanisms have been illuminated by calculating thermal radiation optical parameters including scattering, absorption, and attenuation factors. The result shows fumed silica has low attenuation factor in infrared wavelength range, only 0.00188 for infrared radiation with a wavelength of 3.14 μm. The introduction of SiC can remarkably restrain radiative heat transfer, and the maximum attenuation factor reaches up to 5.848 for infrared radiation with a wavelength of 8.646 μm. The effect of SiC particle size on thermal radiation optical parameters is also studied. The choice of SiC particle size should match up with serving temperature of this insulation. In addition, thermal conductivity measurement has been employed to verify the accuracy of calculation results. Thermal conductivity can significantly decrease from 0.119 to 0.041 W/(m K) at 773 K when 25 wt% SiC (0.877 μm) is added into the composites.